2008
DOI: 10.1186/1477-7827-6-15
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormone regulation of EMP2 expression and localization in the endometrium

Abstract: These findings suggest that targeting of EMP2 to specific locations under the influence of these steroid hormones may be important for integrating the molecular responses required for implantation competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Previous studies have suggested that EMP2 expression is regulated by progesterone (31). As progesterone increases EMP2 expression, we predicted that progesterone treatment may enhance the rate of anti-EMP2 diabody mediated apoptosis in RL95-2 cells as these cells express functional progesterone receptors (34, 35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that EMP2 expression is regulated by progesterone (31). As progesterone increases EMP2 expression, we predicted that progesterone treatment may enhance the rate of anti-EMP2 diabody mediated apoptosis in RL95-2 cells as these cells express functional progesterone receptors (34, 35).…”
Section: Resultsmentioning
confidence: 99%
“…For hormone treatment, RL95-2 cells at 60–70% confluence were washed in PBS, and subsequently incubated with progesterone (Sigma., St. Louis, MO) in treatment medium (DMEM/Ham’s F-12 supplemented with 0.5% charcoal-stripped FBS (Omega Scientific, Tarzana, CA), 1% penicillin-streptomycin, and 1% L-glutamine). Progesterone was and added to treatment medium at 25 μM as previous described (31). Cell viability was determined by trypan blue exclusion.…”
Section: Methodsmentioning
confidence: 99%
“…In normal tissue, EMP2 has a discrete tissue distribution, with high expression in secretory endometrium (10, 11), lung alveolar epithelium (12), and in retinal pigmented epithelium within the eye (13). Dysregulation of EMP2 has been implicated in endometrial cancer, where EMP2 expression correlates with poor prognosis and survival (14), and EMP2 is the only known early diagnostic marker to predict endometrial hyperplasia progression to endometrial cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, another GAS3 family member EMP2 has been detected in the endometrium [25,28,41]. With regard to EMP2 and PMP22, a unique regulatory phenotype has been observed within endometrial cells.…”
Section: Discussionmentioning
confidence: 99%